Ansiedad a la muerte en sobrevivientes de cáncer: análisis psicométrico - Mendoza Tristán, Stephany Yalim (2025)
People with cancer due to a life-threatening illness may present an existential crisis that involves facing their mortality, fear of death, and fear of dying. The aim of this study was to obtain the psychometric properties of validity and reliability of the Templer Death Anxiety Scale in an adult population of Mexican cancer survivors. The design was descriptive cross-sectional with 118 cancer patients who had completed their primary treatment and responded to the Templer Death Anxiety Scale, the fatalism subscale of the Multidimensional Fatalism Scale, and the global health status/quality of life subscale of the QLQ-C30. The results show a 3-factor structure: 1) fear of life coming to an end with 6 items, 2) fear of death with 4 items and 3) fear of dying and illness with 4 items. Adequate reliability values .81 to .83 were obtained and the total scale with 14 items obtained a Cronbach's alpha of .90. A moderate negative and significant correlation was obtained between the total death anxiety scale and its dimensions with indicators of general health, perceived quality of life and age. Significant differences were found between men and women, having children and currently receiving treatment. The death anxiety scale in cancer survivors has psychometric properties suitable for research use.